Translation of Rhetoric in Arabic Preposition in The Text of Al-Qur’an - Azman Che Mat; Ahmad Zulfadhli bin Nokman (Humaniora, 2016)
Preposition was a word that completes the meaning of the verb and noun in the sentence structure of Arabic. The use of prepositions in Arabic was truly significant in understanding the Arabic text, especially holy texts. The question was why prepositions were used in sentences such, whereas the other joints could also give the same meaning? Article presented an analysis of syntax-semantics of prepositions في Fi and علىcAla in al-Quran al-Karim across science of Arabic rhetoric (Balagha). Data were restricted to partial phrase في الضلال and على الهدى ever discussed by Ibn Athir. There are 29 places in the Quran that mention في الضلال and 6 points for على الهدى. Critical analysis based on the discipline of linguistics is expected to expose the use of prepositions in Arabic from the precision and beauty of the Arabic language itself. Summary of the study suggest that research on elements of the rhetoric says that other reasonable tasks highlighted in subsequent studies.